Income inequality in OECD countries : what are the drivers and policy options? - Hoeller, Peter; Joumard, Isabelle; Koske, Isabell (Singapore World Scientific, 2014)
This book offers a comprehensive overview of income inequality across OECD countries in a comparative framework. It examines extensive data on the formation of inequality, identifies clusters of countries with similar income patterns, and explores both ends of the income distribution, including poverty, top incomes, and wealth. The book analyzes key drivers of inequality such as globalization, technological progress, and the impact of various economic policies, particularly in labor markets, taxation, social transfers, and public services. It also addresses the question of whether policies designed to promote economic growth ultimately increase or reduce income inequality.
Includes bibliographical references and index.
Keywords: Tài chính ngân hàng